What the SHO Saw - Dickson, Louise (J R Coll Physicians Lond, 1994)
As discussions about junior doctors' training and duty hours continue, we have looked at the actual 'on take' case load and case mix of a medical senior house officer (SHO) in a district general hospital (DGH) over a six-month period. In our DGH, on a one in four rota, exposure to a few common conditions is high and exceeds the minimum requirements for a post to be approved for general professional training. Limited but useful experience may also be gained in the management of many other conditions. The benefits in terms of structured training and lifestyle resulting from the implementation of the Calman report and the junior doctors' hours initiative need to be set against a possible reduction in patient exposure and in the associated opportunities to learn that may occur with a decrease in SHOs' 'front line' exposure.